UniMAP lateric soil biocoagulant - Wong, Yee Shian; Ong, Soon An; Nabilah Aminah, Lutpi; Norazian, Mohamed Nor; Ragunathan, Santiagoo; Khairul Nizar, Ismail, Prof. Madya Dr.; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (MINDS (Malaysian Invention and Design Society), 2012)
Wong Yee Shian and his team from School of Environmental Engineering won gold for UniMAP lateric soil biocoagulant. 23rd International Invention, Innovation and Technology Exhibition 2012 (ITEX 2012) organized by Malaysian Invention and Design Society (MINDS), 17th - 19th May 2012 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.